2017
DOI: 10.12688/f1000research.10637.1
|View full text |Cite
|
Sign up to set email alerts
|

Health care and social media: What patients really understand

Abstract: Background: Low health literacy is associated with decreased patient compliance and worse outcomes - with clinicians increasingly relying on printed materials to lower such risks. Yet, many of these documents exceed recommended comprehension levels. Furthermore, patients look increasingly to social media (SoMe) to answer healthcare questions. The character limits built into Twitter encourage users to publish small quantities of text, which are more accessible to patients with low health literacy. The present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 7 publications
2
8
0
1
Order By: Relevance
“…Our findings may seem inconsistent with those of prior research because we differentiated among on-line sources whereas previous work generalized across sources potentially obscuring variation by source. We found less use of medical websites but greater use and trust in social media, blogs and celebrity webpages among those with lower health literacy, which may be particularly accessible to this group (Hoedebecke et al, 2017). A second possible explanation is that Internet access and use which has increased over time, has in all likelihood improved among those with inadequate health literacy as well.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our findings may seem inconsistent with those of prior research because we differentiated among on-line sources whereas previous work generalized across sources potentially obscuring variation by source. We found less use of medical websites but greater use and trust in social media, blogs and celebrity webpages among those with lower health literacy, which may be particularly accessible to this group (Hoedebecke et al, 2017). A second possible explanation is that Internet access and use which has increased over time, has in all likelihood improved among those with inadequate health literacy as well.…”
Section: Discussionmentioning
confidence: 85%
“…Lastly, we found that people with lower health literacy preferred sources such as social media and celebrity websites rather than medical websites and government. These sources are updated in real-time and contain brief health messages at lower reading grade levels (Boulos, Maramba, & Wheeler, 2006; Hoedebecke et al, 2017). Social media such as Facebook and Twitter provides opportunities for patients and caregivers to connect with, and support each other (Korda & Itani, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…WONCA members, especially Young Doctor Movement (YDM) members, have masterfully employed social media over the past 5 years in the areas of Family Medicine teaching, leadership, advocacy, and resiliency. [ 12 13 14 ] The lead author (K. H.) envisioned methods of splicing MOOCs and social media to take advantage of both platforms. After navigating through the course options offered by EdX, he found Harvard University's “Improving Global Health: Focusing on Quality and Safety” course.…”
Section: Methodsmentioning
confidence: 99%
“…58 Readability of social media content is particularly important in public health communication during times of crisis as well as in communication of health care information to patients without medical expertise. 59,60 If information is too complex, ambiguous, and at an advanced reading level, it may contribute to decreased patient compliance, worse outcomes, potential for spreading misinformation, and potentially feelings of panic. 59,60 Authors may use various instruments to assess readability of health care content, including the Flesch Reading Ease Score, Reading Grade Level, and Reading Ease.…”
Section: Step 3: Perform Systematic Data Extractionmentioning
confidence: 99%